Analysis of Organizational Resilience Capacity in Accommodation Service Business in Semarang - Muhammad Alif Setiaji; Yustina Erti Pravitasmara Dewi (Jurnal Manajemen dan Organisasi, 2022)
This study aims to comprehensively analyze how to develop human resource management (HRM) practices that create organizational resilience and investigate factors influencing it. This study was done in a qualitative-descriptive manner. Key informants participated in this study – selected based on positions at work and their length of work relevant to the research problems – included HR Manager, HR Coordinator, and Training Manager Assistant of Hotel Ciputra Semarang. The data was collected through in-depth interviews. To examine the data credibility, a triangulation process to the key informants was done. The data was analyzed using a technique proposed by Miles and Hubberman consisting of data reduction, data presentation and conclusion drawing. This study finds that there are 4 HRM practices that can support the organizational resilience, including selective and measurable recruitment, employee compensation, employee training and development, and employee engagement. Further, there are also 4 factors influencing the organizational resilience, namely healthy finance (reserve fund), good employee performance, leadership, and organizational experience.